Manajemen Komunikasi Marketing LAZISNU Kota Bandung - Agi M. Abdul Ghani (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2017)
This study aims to analyze communication management of LAZISNU Bandung to encourage people in handing over charity, management activities undertaken by LAZISNU city, and management LAZISNU in distributing money to the charity (mustahiq). The method used in this study is a phenomenological method, using a qualitative approach. In collecting data techniques this study uses interview, observation, literature review and assessment documentation. The results of this study indicate that the use of communications LAZISNU Bandung to attract people's trust, using two models of communication and marketing, which is the above line and the below line. Event management is performed by lazisnu Bandung already run well, including planning, organizing, monitoring, and NU Skill, NU Preneur, NU Smart, dan NU Care.